Nation Branding: Research Approaches and Models (UNWE Yearbook, 2021)
In theoretical terms the paper makes an overview of the evolution of the concepts of nation brand and reputation management, as defined by contemporary researchers in the relatively young research field of nation branding - Keith Dinnie, Simon Anholt, Gyorgy Szondi, Nadya Kaneva, among others. It outlines the instrumental, political and cultural approaches to the concept and seeks to identify the stakeholders involved - governments and agencies, NGOs, businesses. The assumption is held that Dinnie’s theoretical model provides for a comprehensive conceptualization of nation branding, incorporating the discursive mechanisms of identity construction, which have direct implications for the development of a nation brand strategy and for the enhancement of identity competitiveness.